Involvement of Carboxylesterase in Hydrolysis of Propranolol Prodrug during Permeation across Rat Skin - Harunobu Iwase; Mitsuru Hashimoto; Yuko Takase; Teruko Imai (MDPI AG, 2013)
The use of a prodrug, a conjugate of an active drug with a lipophilic substituent, is a good way of increasing the cutaneous absorption of a drug. However, the activity of dermal hydrolases has rarely been investigated in humans, or experimental animals. In the present study, we focused on the identification of rat dermal esterases and the hydrolysis of a prodrug during permeation across rat skin. We found that carboxylesterase (CES), especially the rat CES1 isozyme, Hydrolase A, is expressed in rat skin and that the hydrolysis of p-nitrophenyl acyl derivatives and caproyl-propranolol (PL) was 20-fold lower in the 9000g supernatant fraction of skin homogenate than in liver microsomes. A permeation study of caproyl-PL was performed in rat full-thickness and stripped skin using a flow-through diffusion cell. Caproyl-PL was easily partitioned into the stratum corneum and retained, not only in the stratum corneum, but also in viable epidermis and dermis. Caproyl-PL could barely be detected in the receptor fluid after application to either full-thickness or stripped skin. PL, derived from caproyl-PL, was, however, detected in receptor fluid after extensive hydrolysis of caproyl-PL in viable skin. Permeation of PL was markedly decreased under CES inhibition, indicating that the net flux of caproyl-PL is dependent on its conversion rate to PL.